Rancang Bangun Aplikasi Absensi Siswa Secara Online Dengan React JS - Roganda Dianju Situmeang; Roberto Kaban; Dewi Yohana Ginting; Asprina Br. Surbakti (Institut Teknologi dan Bisnis Indonesia, 2025)
Attendance is a routine conducted by individuals to indicate their presence or absence in an institution. The attendance system for students at di SMK N 1 Stabat has so far been manually handled by recording attendance in books. This method is time-consuming, often inaccurate, and poses challenges for teachers when compiling reports. To address this issue, an attendance system was designed within the system using QR Code as an assistive tool. With this system, students can simply scan the QR Code on their identity cards to register their attendance. The application was built using the React JS framework with a waterfall methodology. This system also facilitates teachers in creating recapitulation and attendance reports that are directly integrated with students’ parents. Besides saving time, this system is expected to enhance student discipline and prevent proxy attendance practices. SMK Negeri 1 Stabat becomes one of the pioneers in implementing this technology for student attendance, paving the way for similar applications in other institutions.